Photoactive Titania Float for Disinfection of Water; Evaluation of Cell Damage by Bioanalytical Techniques. (25th April 2014) - Shwetharani, R.; Jyothi, M. S.; Laveena, P. D.; Geetha Balakrishna, R.
Abstract A photoactive float was fabricated with the modified titania to cause a feasible disinfection of water, contaminated with E. coli. The commercially available titania was doped with neodymium by pulverization technique to enhance its activity in sunlight and a multiapproach technique was used to evaluate the extended efficiency of the doped sample. X‐ray diffraction patterns depicted the retention of anatase phase on doping and the existence of neodymium was confirmed by the energy dispersive atomic X‐ray analysis and the X‐ray photoelectron spectroscopy. Transmission electron microscopy and Bruner–Emmett–Teller analysis depicted a marginal increase in the particle size and a decrease in the surface area, respectively. Doping induces semiconductor behavior with lower band energy that could respond to visible light and exhibit better disinfection activity. The "f" and "d" transitions of the lanthanide in doped sample caused new electronic behavior of trapping/detrapping effect together with bandgap narrowing. The amount of malondialdehyde, protein, DNA and RNA released on destruction of E. coli was observed to be 0.915 × 10−3 μg mL−1, 859.912 μg mL−1, 20.173 μg mL−1 and 1146.073 μg mL−1, respectively. The above analytical methods along with standard plate count method substantiated the enhanced disinfection efficiency of the doped sample in sunlight.